The stability analysis of the market price using Lambert function method - Jankauskienė, Irma; Miliūnas, Tomas (Lietuvos matematikos rinkinys, 2021)
In this article we are going to analyze market price stability with different market intensity coefficient and delay argument values. Market price is described as a scalar differential equation with a delay argument. In order to find solutions for the transcendental equation we will use method based on Lambert function. We will present examples of the applications of the method.
Keywords: differential equations; delayed arguments; Lambert function; market price